ISOLASI DAN IDENTIFIKASI BAKTERI PADA LIMBAH CAIR PABRIK KELAPA SAWIT DI KECAMATAN LIRIK DAN POTENSINYA SEBAGAI RANCANGAN LEMBAR KERJA PESERTA DIDIK (LKPD) PADA PEMBELAJARAN BIOLOGI SMA - Utari, Melita; Sayuti, Irda; Nursal, Nursal (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2019)
Abstract : The study was conducted aimed at isolation and identification bacteria in palm oil mill effluent in Lirik district from October to December 2018. The results of the study were used to design teaching materials in the form of a Student Worksheet (LKPD) in high school biology learning. This research was conducted in two stages, namely the field research stage and the design stage of teaching materials. The method used in this research is purposive sampling method. Bacterial identification was carried out by macroscopic / morphological observations which included observations of colony shape, colony edges and colony colors, then gram staining and biochemical tests were carried out. The results showed that it was thought that there were 3 genera of bacteria in palm oil mill effluents, the 3 genera of bacteria consisted of genus Enterobacter sp, Pseudomonas sp, and Bacillus sp. The results of this study can be used as a design teaching material in the form of Student Worksheets (LKPD) in biological kingdom monera material in high school.Key Words :Isolation, Identification, Bacteria, Palm oil Mill Effluent, Design Of Student Worksheets